Immediate Breast Reconstruction with Fat-Graft-Augmented ICAP Flaps - Francesco Klinger; Mattia Federico Cavallero; Andrea Vittorio Emanuele Lisa; Fernando Rosatti; Barbara Catania; Marco Klinger; Riccardo Di Giuli; Simone Furlan; Roberta Comunian; Stefano Vaccari; Valeriano Vinci (Life)
Background: Intercostal artery perforator (ICAP) flaps are a reliable option for volume replacement in breast-conserving surgery (BCS), particularly for lower pole defects. However, limited flap volume may reduce their applicability in selected patients. Autologous fat grafting has been proposed to enhance both volume and aesthetic outcomes. Methods: This retrospective study evaluated 10 patients undergoing BCS with immediate reconstruction using fat-graft-augmented ICAP flaps. Nine anterior ICAP (AICAP) flaps and one lateral ICAP (LICAP) flap were employed. The outcomes included flap viability, complications, and aesthetic results over a 6-month follow-up. Results: Partial flap resorption occurred in 2 patients (20%), both of whom were active smokers. No cases of skin necrosis were observed. Fat grafting volumes ranged from 20 to 60 cc. Aesthetic outcomes were satisfactory, with good restoration of the breast contour and stable integration of the flap and grafted fat. Conclusions: The combined use of ICAP flaps and autologous fat grafting is a feasible and effective technique for immediate reconstruction after BCS. It allows volume enhancement, maintains natural contour, and shows low complication rates in properly selected patients. Smoking remains a significant risk factor.